2009
DOI: 10.1203/pdr.0b013e318191fb44
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Stress Response in Small for Gestational Age Neonates

Abstract: There is evidence that adverse conditions during intrauterine development affect future health of the offspring. Hypothalamus-pituitary-adrenal (HPA) axis dysregulation is assumed to play an important role in the association of small for gestational age (SGA) and the pathogenesis of hypertension and the metabolic syndrome. Stress response patterns in SGA neonates may identify a link with intrauterine-induced permanent maladaptation of the HPA axis. Salivary cortisol and cortisone levels were therefore analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…That is important because SGA is a prevalent issue in India (Hofvander, 1982), and it has been argued that it is a key indicator of the health trajectory of a child (Schaffer et al, 2009;Woelfle, 2008). These results also conform with Narendran's, which reported that there were significantly less LBW infants in the yoga group (pb 0.01, 19.12% vs. 30.19%) (Narendran et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…That is important because SGA is a prevalent issue in India (Hofvander, 1982), and it has been argued that it is a key indicator of the health trajectory of a child (Schaffer et al, 2009;Woelfle, 2008). These results also conform with Narendran's, which reported that there were significantly less LBW infants in the yoga group (pb 0.01, 19.12% vs. 30.19%) (Narendran et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…Growth restricted individuals have a differential HPA re- sponse to acute stress when compared to their normal birth weight counterparts (Kajantie et al, 2007;Osterholm, Hostinar, & Gunnar, 2012;Reynolds et al, 2005;Schaffer et al, 2009;Wust, Entringer, Federenko, Schlotz, & Hellhammer, 2005). Similarly to growth restricted individuals, individuals who score high on emotional overeating scores also have a differential HPA axis response to stress (van Strien, Roelofs, & de Weerth, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…12 We applied STATA 9 statistics/data analysis software (Stata Corporation, College Station, TX) for statistical analysis according to Altman's recommendations for repeated measurements that rise from the same individuals studied under different circumstances. 17 Baseline characteristics were compared using the Mann-Whitney test and 2 test when appropriate.…”
Section: Methodsmentioning
confidence: 99%